Relevance of Extra-Institutional Modes of Politicisation Young People - V. O. Vekshin (Управленческое консультирование)
This article examines extra-institutional mechanisms of youth politicisation. The aim of this article is to analyse the relevance of extra-institutional mechanisms of youth involvement in political processes. Methods. The method of scientific literature analysis was used to achieve the set goal. Results. The main mechanisms of politicisation are considered, a  theoretical review of institutions and their role in political life is given. A   description of extra-institutional formats of politicisation is given. Conclusions. The study draws conclusions about the relevance of extra-institutional modes of youth politicisation in modern conditions and shows their advantage over institutional ones. In addition, the paper argues that the use of online platforms is an important way to reach young people and engage them in political processes. The paper is intended for professionals and organisations involved in youth policy.